Pelatihan Leadership dan Kerja Sama Tim untuk Meningkatkan Kepercayaan Diri Siswa - Marhani Marhani; Atika Sahriyanti; Hasruddin Nur; Muhammad Irfan (Al-DYAS, 2026)
Although student leadership development and teamwork training have received considerable attention in various previous studies, research that specifically discusses their role in increasing students’ self-confidence in the school environment remains limited. This study aims to analyze the effectiveness of leadership and teamwork training in increasing students’ self-confidence. This study used a quantitative approach with a pre-experimental design involving 35 students selected through purposive sampling. Data were collected through questionnaires, observation, and documentation and were then analyzed using descriptive statistics and a paired-sample t-test. The results showed that leadership and teamwork training significantly improved students’ self-confidence, communication skills, sense of responsibility, and collaborative attitudes. After participating in the training, students showed greater courage in expressing opinions, participating in group discussions, and taking on leadership roles. The conclusion of this study affirms that leadership and teamwork training play an important role in building students’ self-confidence and social competence in educational settings. These findings provide a theoretical contribution to the development of educational leadership and character education studies, as well as practical implications for educational institutions in designing experience-based leadership and teamwork training programs.